Microencapsulation of Sweet Potato Leaf (Ipomoea Batatas L.) Extract With Different Concentrations of Glucomannan Konjac and Maltodextrin Using Spray Drying Method - Novi Indah Permata Sari; Eni Harmayani; Umar Santoso (Indonesian Food and Nutrition Progress, 2022)
A large amount of phenolic compounds in sweet potato leaves are a potential source of antioxidants. However, polyphenol is sensitive under certain food processing, thereby needs innovation such as microencapsulation to maintain its stability. This study aimed to determine the encapsulation efficiency and characterization of microencapsulation of sweet potato leaf extract using maltodextrin (10% and 20%) combined with Konjac glucomannan (0.5%; 0.75% and 1%). The method used was spray drying using 120 oC inlet temperature. The result showed that the total phenolic compound of sweet potato leaves was 685.06 GAE mg/g extract. The antioxidant activity of sweet potato leaf extract with the DPPH method was 52.80% with an IC50 value of 26.73 ppm. The highest antioxidant activity of the microencapsulated powder sample (10% maltodextrin: 0.75% glucomannan) was 66.84% at a concentration of 100 ppm which had the greatest percent encapsulation efficiency (89.91%).The particle size distribution showed that encapsulated sweet potato leaf extract has a micro-size of around 0.296 µm (78.3%) with good homogeneity of the particle size which can be seen from the Pdi value of 0.304. Therefore, encapsulated sweet potato leaf with 0,75% glucomannan and 10% maltodextrin has the highest encapsulation efficiency and good characteristic.